Technology of teaching foreign language speech to students based on a communicative approach - Grigoreva, Marina Igorevna (The Lingua Spectrum, 2026)
This article examines the technology of communicative teaching of foreign language speech as one of the most effective areas of modern methodology for teaching Russian as a foreign language. This article explores the theoretical foundations of a communicative approach focused on developing communicative competence through training in conditions as close as possible to real-life communication. It describes the key principles of communicative technology: speech focus, functionality, situationality, personal orientation, group interaction, novelty, and modeling of communicative situations. Particular attention is paid to the stages of speech skills development according to E.I. Passov, the interconnected teaching of all types of speech activity, as well as the role of the communicative situation as the main unit of the educational process. It has been shown that the use of interactive methods, role-playing games, problem-solving tasks and text analysis contributes to the development of oral and written speech, overcoming communication barriers, expanding vocabulary and developing the ability to use language as a means of intercultural communication. A conclusion was made about the high efficiency of communication technology in developing students’ speech activity and improving the quality of language training.